The Expression of Colonialism in the Novels of Roch Carrier - Farrauto, Ross Carrie (My University, 1980)
This thesis deals with three novels written by Roch Carrier: La Guerre, yes sir, Il est par la, le Soleil, and Le deux-millieme Etage. The major focus of this study will be the expression of colonialism and the colonial relationship in each novel. The three different aspects of this literary expression will include the relationships between the exploited and the exploiter, and the imagery and language which emphasize these relationships. We shall see how the three different aspects contribute to reinforce the antagonism inherent in the colonial relationship. I will attempt to determine whether an evolution occurs in Carrier's presentation of the colonial relationship, and whether this reflects an evolution in Carrier's attitude towards Quebec's future. A sociological approach, based on Portrait du Colonise by Albert Memmi, will be adopted for this study. References will be made to sociological and literary theory and criticisms.
Keywords: French and Francophone Language and Literature; French and Francophone Language and Literature